Clinical-epidemiological profile of children and adolescents with COVID-19 in Ceará - Ana Nery Melo Cavalcante; Lohanna Valeska de Sousa Tavares; Maria Luiza Almeida Bastos; Rosa Lívia Freitas de Almeida (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to describe the clinical-epidemiological profile of children and adolescents notified by COVID-19 in Ceará. Methods: descriptive epidemiological study from open data repositories of the State Government of Ceará, about cases of OVID-19 in children and adolescents, from 03/15/2020 to 07/31/2020. For data analysis the tests χ2 Pearson, Fisher's exact and Poisson's regression with robust variance were used. Results: 48,002 cases of children and adolescents suspected of COVID-19 were reported, of which 18,180 (8.9%) were confirmed. The median of confirmed cases was 12 years old, 10.5% were newborns/lactants, 10.7% were pre-school children, 21.2% were school children and 57.7% were adolescents. They evolved to death 0.3% of the cases, of which 15% had comorbidities. They needed hospitalization 1.8% of the cases. The highest probability of hospitalization was found in newborns/lactants, male and with comorbidities. Conclusions: most of the confirmed cases occurred in adolescents, however, the evolution of the disease was more severe and with greater need for hospitalization in the age group of newborns/lactants, being the male gender and the presence of comorbidities additional factors for the need for hospitalization.